INTEGRASI GREEN HRM DAN PRINSIP DEI DALAM MEWUJUDKAN ORGANISASI BERKELANJUTAN DAN INKLUSIF - Saputri, Maria Praska (Indragiri Research Center (ingreat), 2025)
This study explores the integration of Green Human Resource Management (GHRM) and Diversity, Equity, and Inclusion (DEI) principles in developing sustainable, inclusive, and innovative organizations, while also preparing future leaders who are adaptable to change. The research highlights the role of green organizational culture as a mediator linking GHRM practices, environmentally focused training, and green innovation—collectively enhancing employee engagement and operational efficiency. Findings indicate that effective GHRM implementation contributes to reducing carbon footprints, optimizing resource management, and fostering workplace diversity. Meanwhile, DEI practices have been shown to improve talent retention, team collaboration, and employee satisfaction, ultimately enhancing overall organizational performance. However, challenges such as resistance to change and work-related stress remain significant barriers that require adaptive and collaborative implementation strategies. Thus, the integration of GHRM and DEI is expected to promote a forward-thinking and sustainable work environment and support the emergence of future leaders with a strong commitment to sustainability.